P2Y2 receptor knock-out mice display normal NaCl absorption in medullary thick ascending limb - Marques, Rita D.; Praetorius, Helle A.; Leipziger, Jens (Frontiers in Physiology, 2013)
Local purinergic signals modulate renal tubular transport. Acute activation of renal epithelial P2 receptors causes inhibition of epithelial transport and thus, should favor increased water and salt excretion by the kidney. So far only a few studies have addressed the effects of extracellular nucleotides on ion transport in the thick ascending limb. In the medullary thick ascending limb (mTAL), basolateral P2X receptors markedly ( 25%) inhibit NaCl absorption. Although this segment does express both apical and basolateral P2Y2 receptors, acute activation of the basolateral P2Y2 receptors had no apparent effect on transepithelial ion transport. Here we studied, if the absence of the P2Y2 receptor causes chronic alterations in mTAL NaCl absorption by comparing basal and AVP-stimulated transepithelial transport rates. We used perfused mouse mTALs to electrically measure NaCl absorption in juvenile (35 days) male mice. Using microelectrodes, we determined the transepithelial voltage (Vte) and the transepithelial resistance (Rte) and thus, transepithelial NaCl absorption (equivalent short circuit current, I’sc). We find that mTALs from adult wild type (WT) mice have significantly lower NaCl absorption rates when compared to mTALs from juvenile WT mice. This could be attributed to significantly higher Rte values in mTALs from adult WT mice. This pattern was not observed in mTALs from P2Y2 receptor knockout (KO) mice. In addition, adult P2Y2 receptor KO mTALs have significantly lower Vte values compared to the juvenile. No difference in absolute I´sc was observed when comparing mTALs from WT and KO mice. AVP stimulated the mTALs to similar increases of NaCl absorption irrespective of the absence of the P2Y2 receptor. No difference was observed in the medullary expression level of NKCC2 in between the genotypes. These data indicate that the lack of P2Y2 receptors does not cause substantial differences in resting and AVP-stimulated NaCl absorption in